Visual Culture and Visual Literacy - Sibel Onursoy (Türk Kütüphaneciliği)
Recently visual literacy gains importance in the context of understanding the rising visual culture products, thinking about them and producing these products. The purpose of this article examines the concept of visual literacy that is the relationship with visual culture depending on the literature. Visual literacy is one of the multiple literatures that emerge from the development of information and information dissemination forms. Visual literacy is an interdisciplinary concept and associated with some areas, such as graphic design, visual arts, architectural engineering, industrial product design, visual communication and media literacy. Visual culture covers every human product, so visual products that we face in everyday life and visual realities with abundant alternatives constitute our daily life itself. Sometimes, this confusing visual understanding creates a gap between contemporary cultural richness and what can be observed.